Exploring trade unions awareness and roles in combating forced labor in Malaysia - Ismail, Fadillah; Mohd Angsor, Mohd Asmadi; Mohd Yusof, Halimah; Ahmad, Nazilah (2024)
Forced labour is a serious issue affecting various industries, and trade unions play a crucial role in protecting workers from exploitation. Globally, this issue impacts millions of workers, particularly in sectors such as manufacturing, agriculture, and construction. It often involves coercion, exploitation, and violations of human rights, leading to significant social and economic challenges. Despite international efforts to address this issue, forced labour practices still persist in many countries, including Malaysia. Therefore, this study examines trade unions' awareness and role in combating forced labour in Malaysia. Its primary objectives are to assess union members’ understanding of forced labour and the specific actions taken by unions to address this issue. The research employed a qualitative approach, using semi-structured interviews with ten union members from various sectors, including the Royal Malaysian Customs Department and universities. The interviews were transcribed and analysed using NVivo software, which identified key themes through thematic analysis. The findings indicate a range of awareness levels among union members. Some could identify subtler forms of forced labour, such as overtime resulting from inadequate staffing, while others associated forced labour solely with severe exploitation, such as slavery. The study also reveals that, while unions are strong advocates for workers' rights, their ability to address forced labour is constrained by limited resources and reliance on management. Based on these findings, the study recommends enhancing staff training, improving communication channels for reporting labour issues, and establishing partnerships with external organisations to strengthen union efforts. Further research is needed to evaluate the effectiveness of union-led interventions and the impact of educational initiatives in different sectors. Additionally, employer and policymaker involvement is essential to bridge gaps that allow exploitation to persist. Understanding the role of unions in addressing forced labour is crucial to improving their effectiveness and protecting workers from exploitation through actionable recommendations